An aggregated technique for optimization of SOAP performance in communication in Web services. Issue 3 (September 2016) - Senagi, Kennedy; Okeyo, George; Cheruiyot, Wilson; Kimwele, Michael
Abstract Simple Object Access Protocol (SOAP) among other techniques implements Web Services (WS). SOAP offers a lightweight and simple mechanism for exchange of structured and typed information among computing devices in a decentralized, distributed computing environment. However, SOAP transmits data in Extensible Markup Language (XML) format. XML documents are huge in size and verbose thus becoming a major hindrance in performance for high-performance applications that process lots of data. In this paper, we develop, implement and evaluate SOAP performance optimization aggregated architecture in a disadvantaged network, i.e., 10 Mbps bandwidth. The aggregated architecture entailed: client side caching, document–literal Web Services Description Language (WSDL) description, simple database queries on the server side and Gzip compression technique. The experimental results showed a relatively high turnaround time and low network throughput. Nevertheless, improved performance of SOAP is evident in terms of bandwidth utilization and transfer time. This can be useful in disadvantaged networks.